Rescue of an asymptomatic arterial occlusion after kidney transplant. Issue 2 (7th February 2022) - Kadakia, Yash; Hwang, Christine; MacConmara, Malcolm
Abstract : Arterial injury leading to vascular occlusion is a rare complication of kidney transplantation that requires urgent intervention to salvage the kidney and prevent graft loss. Occasionally, the recipient iliac vessels may be injured, resulting in acute ischaemia of the lower extremity in addition to loss of blood flow to the kidney transplant. In the case presented here, a 58-year-old man with chronic kidney disease secondary to IgA nephropathy underwent pre-emptive deceased donor renal transplantation complicated by an external iliac artery (EIA) dissection proximal to the transplant anastomosis. However, as a result of retrograde blood flow from collateral vessels, perfusion of the kidney and right lower extremity was initially preserved and early diagnosis was made after post-transplant ultrasound. This report reviews the aetiology, clinical features and therapeutic options for arterial injuries post-transplant. This case also highlights the importance of post-transplant vigilance and the value of routine postoperative ultrasound imaging.